2019
DOI: 10.1186/s12948-019-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

IgE level in newborn umbilical cord and its relationship with some maternal factors

Abstract: Background and objectives Allergic diseases are among major pediatric issues as they are highly prevalent and chronic. Therefore, identification of factors contributing to allergic disease could play a significant role in prevention of these conditions. This study aimed at investigating the IgE level in newborn’s umbilical cord blood and its relationship with some maternal factors. Methods A cross-sectional study was conducted in 101 mothers and their newborns in Babol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
5
4
0
Order By: Relevance
“…Our study showed that newborn gender was positively correlated with CB-IgE levels. Consistent with our findings, Petrovičová et al, 21 De Amici et al, 8 Iraj Mohammadzadeh et al, 16 Scirica et al, 22 and Chien-Han Chen et al 23 also found that the CB-IgE level was higher in male newborns, possibly because of interaction between interleukin-13 (IL-13) and CB-IgE, which is modified by male sex. 24 And CB-IgE levels might reflect early differences in immune system development and function between boys and girls that contribute to the known predominance of asthma and related symptoms among boys rather than girls before puberty.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study showed that newborn gender was positively correlated with CB-IgE levels. Consistent with our findings, Petrovičová et al, 21 De Amici et al, 8 Iraj Mohammadzadeh et al, 16 Scirica et al, 22 and Chien-Han Chen et al 23 also found that the CB-IgE level was higher in male newborns, possibly because of interaction between interleukin-13 (IL-13) and CB-IgE, which is modified by male sex. 24 And CB-IgE levels might reflect early differences in immune system development and function between boys and girls that contribute to the known predominance of asthma and related symptoms among boys rather than girls before puberty.…”
Section: Discussionsupporting
confidence: 90%
“…14 Most studies have shown that elevated CB-IgE levels have a role in the future development of allergic diseases. 4,5,[15][16][17][18] For example, elevated CB-IgE has been a useful measure of subsequent risk of food allergy/ urticaria at 12 months 19 and a cohort study showed that the risk of allergy development at the age of 4 (OR = 2.92) and 10 (OR = 1.73) was significantly correlated with increased IgE level in newborn umbilical cord blood. 20 Hence, CB-IgE level is believed to be correlated with allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the delivery method did not signi cantly in uence the total IgE levels in the umbilical cord. That is similar to a Mohammadzadeh et al study in Iran 2019 [10]. In contrast, Petrovičová et al study in that reported the total IgE level in the umbilical cord was higher in newborns born by cesarean section than those born via vaginal birth.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with our ndings, krimi et al 2012 also found that the total IgE level in umbilical cord blood did not association with newborn gender [9]. These ndings are in contrast to Mohammad zadeh et al study in Iran 2019 which found signi cantly higher levels of total IgE in umbilical cord were seen in male newborns [10]. Higher levels of total IgE in male newborns might be related to a higher prevalence of atopy and allergic diseases in boys [11].…”
Section: Discussionsupporting
confidence: 85%